Editorial: Creating Capabilities for Socially Vulnerable Youth in Europe - Susanne Gottuck; Hans-Uwe Otto (Social Work & Society, 2014)
Political, economic and social transformations in Europe have affected harshly a growing number of young people, who are currently experiencing social disqualification and disaffiliation, particularly so during the critical transition from school to work. This special issue gives an account of the results of the Marie Curie ITN EduWel. It provides robust research on education and welfare by evaluating capacities to tackle the multiple challenges and pressures that a large proportion of young people in Europe faces today.